MANAJEMEN STRATEGI DALAM MENINGKATKAN KEMAMPUAN TPACK GURU SEKOLAH DASAR DAN MENENGAH - Deden, Deden Yudi; Desita Purwanti Sundar; Rina Farida Aryani; Wiwik Dyah Aryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid development of digital technology has changed the world of education, requiring teachers to have Technological Pedagogical and Content Knowledge (TPACK) competencies in order to effectively integrate technology in learning. This study aims to analyze strategic management practices in improving teachers' TPACK capabilities at the primary and secondary school levels. Using a descriptive qualitative approach with a case study method, data were obtained through interviews, observations and document analysis in three schools in Bandung district. The results showed significant variations in the aspects of strategic planning, implementation and evaluation between schools. Elementary school teachers demonstrated the most comprehensive management model, with structured strategy planning, continuous thematic training, and evaluation using TPACK-based observation rubrics. Meanwhile, junior and senior high school teachers showed a sporadic and less contextualized approach. Supporting factors include the principal's leadership, IT team support, technology infrastructure and collaborative culture. The main barriers were administrative burden, digital literacy gap, and lack of continuous evaluation. This study concludes that effective TPACK development requires a structured, collaborative and evaluation-based managerial strategy, supported by adaptive and innovative leadership and a learning ecosystem.